A Study on the Implementation of Dynamic Routing Algorithm to Improve Efficiency for Wireless Sensor Networks - Choi, Won Hyuck; Jie, Min Seok (Applied Mechanics and Materials, 2013)
The development of wireless communication and electronic technology leads to wireless sensor networks in various fields. Wireless sensor networks can exchange the data that generated from near environment field observation between other sensor nodes. Generally, Wireless sensor networks consist of multi sensor nodes and one or more sink nodes The sensor sensing data that nodes detected transmit from sensor networks to base station and deliver to users through internet. However sensor networks are restricted in the aspects of communication, processing data and energy consumption. Because of the low capacity batteries with devices of sensor networks, it is important to increase the lifespan operation life of sensor nodes by using energy efficiently. In this kind of sensor nodes, the energy consumption for message sending and receiving is very important for the maintenance of sensor nodes. In the existing static routing method, it consumes more energy for the maintenance of sensor network than dynamic routing method because data transmits repeatedly when the sensor data begin to spread. In this study, based on the difference in the cycle of information gathering in accordance with the characteristic of the sensor in sensor network and the cycle of demands from the sink in accordance with the characteristic of application layer, dynamic routing of wireless sensor network is proposed which actively responds to its various needs.